Making Nonwoven Fibrous Poly(ε‐caprolactone) Constructs for Antimicrobial and Tissue Engineering Applications by Pressurized Melt Gyration. Issue 8 (2nd May 2016) - Xu, Zewen; Mahalingam, Sunthar; Basnett, Pooja; Raimi‐Abraham, Bahijja; Roy, Ipsita; Craig, Duncan; Edirisinghe, Mohan
Abstract : This work is about novel manufacturing of polycaprolactone nonwoven scaffolds for application in tissue engineering and as antimicrobial mats. The process makes use of rotation speed of an aluminium cylindrical vessel, working pressure, and the temperature to jet out the fibrous products on a large scale. Abstract : A pressurized melt gyration process has been used for the first time to generate poly(ε‐caprolactone) (PCL) fibers. Gyration speed, working pressure, and melt temperature are varied and these parameters influence the fiber diameter and the temperature enabled changing the surface morphology of the fibers. Two types of nonwoven PCL fiber constructs are prepared. First, Ag‐doped PCL is studied for antibacterial activity using Gram‐negative Escherichia coli and Pseudomonas aeruginosa microorganisms. The melt temperature used to make these constructs significantly influences antibacterial activity. Neat PCL nonwoven scaffolds are also prepared and their potential for application in muscular tissue engineering is studied with myoblast cells. Results show significant cell attachment, growth, and proliferation of cells on the scaffolds.